Impact of trust promotion and perception of ease of use on the decision making of the use of ShopeePay in Mega Regency Houses - Firsta Rifsi Mey Atshari; Primaraga Sumantri Indra Wicaksana (Enrichment : Journal of Management, 2023)
The purpose of this research is to answer questions like Does promotion affect ShopeePay users' decisions to adopt digital wallets? and Does trust affect such decisions?Does the adoption of shopeePay digital portfolios depend on how convenient people perceive it? ShopiePay can enhance the efficiency of their marketing campaigns to reach more potential consumers by being aware of the aspects that customers in the region take into account when choosing to use these payment systems.This type of research is quantitative with 3 independent variables consisting of belief (X1), promotion (X2) and perceived convenience (X3) and the dependent variable usage decision (Y). The illustrations were taken using the Lemeshow procedure and the population was 98 residents and illustrations of 100 residents were obtained. The information collected was then analyzed using the Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, Hypothesis Test and the coefficient of determination, with the help of the SPSS Version 22 For Windows program. The research results can be seen that belief, promotion, and perceived ease of use significantly influence the decision to use. This is confirmed by the T test. T count= 6. 402 with a significance of 0. 000<0. 05 so the hypothesis can be accepted. The results of the research show that trust, promotion and the perceived ease of use have influenced the decision to use ShopeePay in Mega Regency housing. So that the industry must be able to give confidence to consumers and provide attractive promotions on television and other media. The industry must also be able to pay attention to the convenience in the application by providing complete instructions for its users.